She's gone ebook - Bell, David (2022)
A new page-turning thriller from USA Today bestselling author David Bell. When a girl disappears, who do you suspect? When 17-year-old Hunter Gifford wakes in the hospital on the night of homecoming, he's shocked to learn he and his girlfriend, Chloe Summers, have been in a terrible car accident. Hunter has no memory of the crash, and his shock turns to horror when he is told Chloe's blood has been found in the car—but she has disappeared. Back at school, his fellow students taunt him, and his former best friend starts making a true-crime documentary about the case—one that points the finger directly at Hunter. And just when things can't get any worse, Chloe's mother stands in front of the entire town at a candlelight vigil and accuses Hunter of murder. Under mounting pressure from the police, Hunter takes matters into his own hands by questioning anyone who might know the truth and posting videos to prove his innocence. When Hunter learns he and Chloe were seen arguing loudly outside the dance, he faces a sickening possibility. Was he angry enough to kill the person he loved? Praise for David Bell: "David Bell is a top-notch storyteller and Layover is his best book yet. I flew through this twisty, riveting psychological thriller at breakneck speed, hooked from the first page right up through the book's breathless conclusion."—Cristina Alger, New York Times bestselling author of Girls Like Us "With hints of Patricia Highsmith's THE TALENTED MR. RIPLEY, this is a riveting thriller." —Palm Beach Daily News "Readers will find themselves thoroughly immersed in this riveting thriller...both compelling and surprising."—Booklist "Bell is a brilliant craftsman as well as storyteller."—The Providence Journal